GLOBALISATION AND THE QUESTION OF LOYALTY IN AFRICA:A PHILOSOPHICAL REFLECTION - Omotoyinbo, Femi R (International Review of Humanities Studies, 2021)
The focus of this study is on the influence of globalisation on the patriotic loyalty of Africans to Africa. Existing discourse is quite thin regarding the relationship between globalisation and loyalty in Africa. Yet, examining such relationship is important to understand the dearth of desirable development in many African states. Taking a philosophical approach, the contention in this study is that patriotic loyalty, which is significant for development in Africa, has been distorted by the influx of globalisation into Africa. The study historically highlights how globalisation influences diversion of loyalty from the immediate community to the global community. While the purpose of the study is not to encourage disloyalty to the global community, the emphasis, however, is that loyalty to the global community should not be to the detriment of local ties. Among other things, it is argued that such could result in detachment from core norms and values and the weakening of local ties which are necessary for sustainable development at the local levels. The study acknowledges the impossibility of reverting Africa to a pre-globalised period and concludes with some suggestions for developing, encouraging and sustaining loyalty in the continent.